The accession of Latin American countries to the Asian Infrastructure Investment Bank: lessons from Brazil and Chile. Issue 3 (28th April 2020) - Urdinez, Francisco
Abstract : Purpose: The purpose of this paper is to discuss the motivations behind the accession of Latin American countries to the Asian Infrastructure Investment Bank (AIIB) with a focus on the cases of Brazil and Chile. Design/methodology/approach: The author collected data using a case study methodology, primarily through semi-structured interviews with decision-makers and through official government documentation. Findings: The findings identified that, overall, the Brazilian politicians who made the decision to join the bank had an unclear perception of its economic benefit and believed that the clearest benefit from accession is political (to support China's initiative). After years of domestic political turmoil and economic crisis, Brazil experienced delayed incorporation into the bank, slow ratification processes in the domestic arena and a reduction in its capital commitment. Chilean decision-makers, on the other hand, seemed to have a clearer idea of the benefits from accessing the bank, which explains that their ratification process has been faster and smoother. Yet, a surprising socio-political crisis delayed incorporation into the bank. Both countries have delayed their accession to the bank due to domestic crises. Practical implications: Three policy implications can be drawn from this study. First, the entry of Latin American countries into the bank reflects the persuasiveness of Chinese diplomacy in this region. Second, the author finds that interviewees are not always able to differentiate the AIIB from the Belt and Road Initiative (BRI) and hold the misguided idea that the AIIB is subordinated to the BRI rather than complementary to it. This might set overly high expectations of the benefits of entering the AIIB. Third, the author foresees that the largest potential of the AIIB in Latin America lies in the possibility of participating in co-financed projects, in particular with the Inter-American Development Bank and the Development Bank of Latin America. Originality/value: Research on the AIIB has boomed in recent years, yet there are few in-depth studies about Latin American prospective members. The value of this study lies in offering in-depth data for two of the eight prospective members from this region.